Tantangan dan Keberhasilan Program Eliminasi Malaria di Wilayah Endemik: Tinjauan Pustaka - Landudjama, Leni; Noviana, Ineke; Gunawan, Yosephina E S; Hara, Maria Kareri; Kitu, Irene Febriany Mamo (Poltekkes Kemenkes Kupang, 2023)
Background: Malaria is a disease caused by the plasmodium parasite transmitted to humans through the bite of an infected female Anopheles mosquito. The high malaria endemic area is concentrated on Sumba Island. Aim: To identify the challenges and successes of malaria elimination programs in endemic areas. Method: This research is a literature review. The literature search process uses the Google Scholar database with the keywords 'Challenges and Successes of Malaria Elimination Programs in Endemic Areas'. Inclusion criteria are journals published in the 2022-2023 period, journal article types with quantitative, qualitative research methods and review results, journals can be accessed in full via full text pdf files, articles taken are national and international journal articles. Results: The challenges of malaria elimination programs in endemic areas are increasing resistance to treatment, decreasing vaccine efficacy, Human resources, infrastructure and supporting equipment are still lacking in quantity and quality, limited funding, weak community involvement programs, multisectors and stakeholders, geographical conditions, geology and community behavior. The success of malaria elimination programs in endemic areas by increasing capacity, capability, regional and national resilience, health and technical human resource competencies and leadership in disease control, expanding multisectoral initiative programs, holistic quality approaches involving individuals/ families/ communities, increasing investment in research and development of potentially transformative technologies used in malaria elimination programs. So, national and international multisectoral cooperation needs to be improved so that the target of eliminating malaria is achieved.